Sistem Komparatif Indonesia Dan Korea Selatan: Pengawasan Peredaran Produk Kecantikan Di Platform e-commerce - Nurhidayah Nurhidayah; Muhammad Syaifuddin; Suci Flambonita (CV. Ulil Albab Corp, 2026)
The uncontrolled circulation of beauty products lacking official registration permits within Indonesia's rapidly expanding e-commerce ecosystem has emerged as a pressing legal and public health concern. The structural weakness of existing oversight instruments, combined with ambiguous legal obligations assigned to digital platform operators, creates regulatory gaps that are routinely exploited by irresponsible business actors. This study aims to examine and compare the oversight mechanisms governing the distribution of beauty products on e-commerce platforms between Indonesia and South Korea, employing a normative legal research method with a comparative approach. Primary legal materials were drawn from statutory regulations, government decrees, institutional regulations, and official policy documents from both jurisdictions. The findings demonstrate that Indonesia currently lacks an independent cosmetics act, causing regulatory authority to remain fragmented across multiple sectorally unintegrated instruments. In contrast, South Korea established a comprehensive and adaptive Cosmetics Act that explicitly designates platforms as active oversight partners, supported by a risk-based product classification system and robust institutional coordination. These comparative findings underscore the urgent need for Indonesia to pursue three strategic reforms: enacting a standalone cosmetics law, adopting a risk-differentiated product classification framework, and strengthening the legal obligations of e-commerce platforms as active gatekeepers in the national consumer protection system.